Primary mediastinal Ewing’s sarcoma presenting with sudden and severe chest pain: a case report - Su, Chen; Zhu, Xiaobo; Zhang, Junjie (Frontiers in Oncology, 2024)
Ewing's sarcoma, characterized by small round cell morphology, is a rare malignancy, with mediastinal Ewing's sarcoma being even less common. This case describes a distinctive presentation of mediastinal Ewing's sarcoma in a 32-year-old male presenting with sudden and severe chest pain. Initial evaluation excluded cardiac and pulmonary emergencies, revealing a posterior mediastinal mass through advanced imaging. The patient's clinical symptoms significantly improved following the complete resection of the tumor via thoracoscopy. Subsequent analysis incorporating imaging, histological, immunohistochemical and genetic findings led to the conclusive diagnosis of primary mediastinal Ewing's sarcoma.